Mechanical properties of fibre metal laminates reinforced with carbon, flax and sugar palm fibre-based composites - Muthukumar, Chandrasekar (2019)
Fibre metal laminate (FML) consists of sheet metal and fibre prepreg stacked alternatively in 2/1 or 3/2 lay-up and cured to form the laminate. The commercially available FML such as CARALL (Carbon fibre reinforced aluminum metal laminate), GLARE (Glass laminate aluminum reinforced epoxy) and ARALL (Aramid fibre reinforced aluminum metal laminate) based on the synthetic fibres have limitations like difficulties in recycling, degradability and disposal problems. These factors push the need for environment friendly material. From the literature review, it has been identified that the studies on the natural fibre reinforced FML and the metal surface treatments other than the standard chromic acid anodizing are limited. Also, the impact of aging effects on the mechanical properties of natural fibre reinforced FML has never been studied. In this research, a new class of FML reinforced with the carbon fibres and natural fibres like flax and sugar palm has been fabricated using the hand lay-up and hot press technique. Their mechanical properties under various loads with respect to the metal surface treatment, fibre stacking sequence, hygrothermal and sub-zero aging effects were studied. Based on the results from the experiments, it could be seen that sanding followed by silane treatment could be used as a metal surface treatment for FML, as it provides superior properties over the FML with sanded metal surface. Among the studied configurations, FML with the pure flax fibres exhibited the highest strength, stiffness and fatigue life. Hybridization of flax with sugar palm also has led to significant improvement in the properties compared to the FML with sugar palm fibres. On the other hand, FML specimens exposed to the aging under the moisture/temperature, failed at lower loads, possessed lower strength and stiffness than the unexposed or dry specimens. The degradation in properties was more severe in case of hygrothermal conditioning than the sub-zero exposure. This is because hygrothermal conditioning resulted in 6-8% increase in thickness swelling due to the moisture absorption by natural fibres in the laminate, weakening of the interfacial bonding strength and degradation of the natural fibre reinforced composite ply as evident from the presence of multiple cracks in the microstructure of the hygrothermally aged FML specimens. To summarize, FML with the pure flax fibres has shown better mechanical properties; longer fatigue life and fibre bridging effect which is critical to sustain larger number of cycles before the failure. The degradation in mechanical properties and physical changes in the FML due to the aging indicates the need to evaluate their behavior if they are required to use in the structures operating under such environmental conditions.